Calcified nodule of Winer. - Colonna, V. (European Journal of Pediatric Dermatology, 2015)
In the newborn the most frequent causes of cutaneous calcification are idiopathic calcinosis, the nodule of Winer, iatrogenic calcifications due to extravasation of calcium salts and dystrophic calcification as that resulting from neonatal subcutaneous fat necrosis or acupuncture of the heel. The most frequent site of the nodule of Winer in the neonatal period is the ear lobe (1). This is why some textbooks (2) cite it as the calcified ear nodule. The pathogenesis of this lesion is not defined, but many Authors believe that it is a dystrophic calcification secondary to various causes as milia, hamartomas of the sweat glands, nevi or trivial trauma. The diagnosis should be suspected clinically for the warty surface, the yellow discoloration and hard consistency and confirmed by histological examination consequent to removal with curette.